Continuous and High Transport of Particles and Solutes by Benthos in Coastal Eutrophic Sediments of the Pomeranian Bay - Powilleit, Martin; Forster, Stefan (Frontiers in Marine Science, 2018)
We present results on bioirrigation and reworking of sediments by benthic macrofauna in sediments of the Pomeranian Bay (southern Baltic Sea), that were obtained ~22 years ago. The investigation took place at four stations ranging from 9 – 19 m water depth, which we observed between 1993 and 1995 over the course of 30 months. In order to assess exchange of solutes across and particles from the sediment-water interface with the underlying sediments, we used bromide as ex situ tracer for bioirrigation and chlorophyll a equivalents as in situ tracer for particle reworking. Using models to interpret tracer distributions in the sediment, we compare the magnitudes of small scale, diffusion – like, versus relatively large-scale, non-local, transport modes. Our results indicate a spatial differentiation of the bay: the coastal station most heavily impacted by eutrophication close to the Oder River mouth showed medium reworking and intense bioirrigation combined with lower chlorophyll concentrations throughout the sediment. This contrasts with high surface pigment concentrations at the shallow Oder Bank station, indicating benthic primary production and intense particle mixing.Medium local particle reworking at the northwestern station and medium mean solute transport rates characterized the two deeper stations in the northern Bay. The bromide tracer experiments, which exclusively depict animal activity, showed significant biological solute transport to ~10 cm sediment depth within 3 days. Non-biological transport mechanisms in the field (e.g. resuspension, fishing activity) might additionally affect the in situ tracer chlorophyll a - depth distributions. This tracer, too, indicates mixing within the uppermost 10 cm of the sediment within ~2-3 months. In general, experimentally obtained solute transport constants were higher than most values reported previously (surface : 155 yr-1) and particle reworking was at the high end of reported values as well. Thus, benthic fauna is responsible for an intense bioturbation in Pomeranian Bay. Specifically, high bioirrigation rates were associated with high density and biomass of deep burrowing polychaetes. Recently published rates of particle reworking in the area are on the same order of magnitude as ours obtained two decades ago.This finding is consistent with the species composition which generally remained the same